The Effect of Human Capital, Total Assets, Total Liabilities on the Net Income of a Company - Surbakti Karo-Karo; Jihen Ginting (Randwick International of Social Science Journal, 2020)
The problem in this study is that every company wants low costs and high profits for the company, every employee wants a high salary/wages for payment of performance, also how much influence the assets and debts of the company in providing net profit for the company. This study aims to determine the effect of Human Capital, Total Assets and Total Liabilities on the company's Net Profit in companies listed on the Indonesia Stock Exchange LQ-45 index. The sampling method used was purposive sampling, with a total sample of 27 companies, for 2017-2018 there were 54 samples. The results show that Human Capital, Total Liabilities and Total Assets simultaneously have a significant effect on company net income.